A study on the distribution of different carnitine fractions in various tissues of bovine eye - Siddiqi, N. J.; Alhomida, A. S.; Khan, H. A.; Ong, W. Y. (Cellular and Molecular Biology, 2012)
The aim of the present investigation was to study the distribution of various carnitine fractions in different bovine ocular tissues. Different ocular tissues were homogenized and their carnitine content was determined. The carnitine fractions studied include short chain carnitine, long chain carnitine, acyl carnitine and free carnitine. All the four carnitine fractions were found to be present in all the ocular tissues studied. Iris contained the highest concentration short chain, long chain and acyl carnitine. However significant (p < 0.05) differences existed in long chain and acyl carnitine between iris and other tissues. Free carnitine was found in highest concentration in ciliary body which was significantly higher when compared to lens nucleus (p < 0.05). There was no significant difference in the carnitine fractions between aqueous and vitreous humor. These results show differential distribution of carnitine in bovine ocular tissues which may be involved in various functions besides fatty acid oxidation.